Corporate Social Responsibility and Corporate Governance: a Bibliometric Analysis Study - Muhammad Fakhrurrazi; Mahmud Mahmud (Eduvest - Journal of Universal Studies, 2025)
The aim of this study is to evaluate the domestic wastewater management system currently implemented in Banjar Regency. The river water quality was analyzed using the STORET method by comparing sampling results with the applicable water quality standards, while data on sanitation access were obtained from the Banjar Regency Government. SWOT analysis was used to assess the current state of domestic wastewater management in the region. The results of the STORET analysis indicate that water quality in the Martapura Sub-watershed has improved due to government programs related to domestic wastewater treatment and management. Data on access to domestic wastewater facilities show that most residents have independently owned toilets, supported by government programs that assist low-income communities in gaining access to domestic sanitation facilities. The SWOT analysis highlights the need for improved management practices among the Beneficiary and User Groups (KPP), who serve as operators in each village.